Características fisiológicas e agronômicas do trigo em função da combinação de matéria orgânica estabilizada, Azospirillum brasilense e doses de nitrogênio - Rodrigues, Luan Fernando Ormond Sobreira (2013)
Brazil has a low contribution to the production of wheat in relation to world stage. Therefore, some techniques have been developed to increase the productivity of wheat grains in the country and reduce production costs. Among these techniques, we can highlight inoculation with plant growth promoting bacteria which contribute both to the biological nitrogen fixation in non-legumes, as with the release of plant growth regulator to the roots of the plants in which they associate. However, the biological nitrogen fixation by these bacteria is not sufficient for maximum yield of these crops and it is necessary, therefore, association with some other technique such as spraying organic material stabilized in humic acid, it may be a viable alternative in the process production of wheat. Given the above, the aim of this work was to verify the agronomic effectiveness of the combination of Azospirillum brasilense in relation to or associated with the use of humic acid and different levels of nitrogen fertilizer in wheat crop conditions in the greenhouse and field. Three experiments were conducted, two simultaneously in the agricultural year 2011/2012, in the greenhouse and in a field experiment in the agricultural year 2012/2013. Both experiments were carried out in experimental stations belonging to the core of experimental stations Unioeste, from Marechal Cândido Rondon, PR. The experimental design was randomized blocks in a 4x4 factorial with four replications. The first factor relates to plant growth promoters (Control; Ab-V5 strain of A. brasilense; organic material stabilized humic acid HA and Ab-V5+HA) and the second factor levels of nitrogen (0, 30 , 60 and, 90 kg ha-1 of N). Was used as plant material wheat cultivar CD 150, which evaluated the plant height, dry weight of leaves, stems and sheaths, reproductive structures and shoots, leaf area, leaf gas exchange measurements, SPAD , yield components and grain yield of the crop. In general, home vegetable was observed that the combined use of Ab-V5+AH, favored the increase in dry matter of shoots, the absorption of N and K, the leaves, and P and K, the grains wheat, number of ears per pot, the average length of the ears and the weight of one hundred grains. In the field experiment showed that Ab-V5+HA promoted increase in shoot dry matter, gas exchange, the K content of grain, and the number of ears per square meter. The grain yield of the crop was influenced by any of the treatments under greenhouse and only levels of nitrogen in field experiment. The conclusion of this work that the combined use of Ab-V5+AH favors the growth characteristics of wheat crop, but more studies are needed because grain yield is only influenced by nitrogen fertilizer rates